The Immediate Effects of Different Types of Augmented Feedback on Fast Walking Speed Performance and Intrinsic Motivation After Stroke - Saleh M. Alhirsan, PT, MSc, PhD; Carmen E. Capó-Lugo, PT, PhD; Christopher P. Hurt, PhD; Gitendra Uswatte, PhD; Haiyan Qu, PhD; David A. Brown, PT, PhD (Archives of Rehabilitation Research and Clinical Translation, 2023)
Objective: To examine the immediate effects of different types of augmented feedback on walking speed and intrinsic motivation post-stroke. Design: A within-subjects repeated-measures design. Setting: A university rehabilitation center. Participants: Eighteen individuals with chronic stroke hemiparesis with a mean age of 55.67±13.63 years and median stroke onset of 36 (24, 81) months (N=18). Interventions: Not applicable. Primary outcome: Fast walking speed measured on a robotic treadmill for 13 meters without feedback and 13 meters with augmented feedback on each of the 3 experimental conditions: (1) without virtual reality (VR), (2) with a simple VR interface, and (3) with VR-exergame. Intrinsic motivation was measured using the Intrinsic Motivation Inventory (IMI). Results: Although the differences were not statistically significant, fast-walking speed was higher in the augmented feedback without VR (0.86±0.44 m/s); simple VR interface (0.87±0.41 m/s); VR-exergame (0.87±0.44 m/s) conditions than in the fast-walking speed without feedback (0.81±0.40 m/s) condition. The type of feedback had a significant effect on intrinsic motivation (P=.04). The post hoc analysis revealed borderline significance on IMI-interest and enjoyment between the VR-exergame condition and the without-VR condition (P=.091). Conclusion: Augmenting feedback affected the intrinsic motivation and enjoyment of adults with stroke asked to walk fast on a robotic treadmill. Additional studies with larger samples are warranted to examine the relations among these aspects of motivation and ambulation training outcomes.